Reassembling the Field-based Applicability of the Lactate Threshold for Old Age - Garcia-Tabar, Ibai; Ruiz-Rios, Maitane; Martinez-Labari, Cristina; Maldonado-Martin, Sara; Murias, Juan Manuel; Gorostiaga, Esteban M. (International Journal of Sports Medicine, 2024)
This study aimed to investigate the applicability of the Lactate Threshold (LT) to predict maximal oxygen uptake (˙VO2max) and demarcate the boundary between the moderate- to heavy-intensity domain (HRm-h) in old age in comparison to the most utilized methods. A cross-sectional validation study was conducted. Participants aged 61 to 77 performed a familiarization procedure, an incremental maximal exercise treadmill test (CPX) for ˙VO2max determination, the Six-minute Walk Test (6MWT), and a discontinuous incremental field test for LT determination. Lower (P<0.01) internal effort was required for LT testing (76±8%HRmax) compared to 6MWT (92±9%HRmax). The application of the 6MWT reference equations overestimated ˙VO2max by 10–23%. LTs better estimated the ˙VO2max (r ≈0.90, SEE: ≈3.0] compared to the 6MWT (r=0.68, SEE=5.5). HRm-h determined by the CPX differed (20%; P=0.001) from that obtained by LT. HRm-h stratification indicated participants fall into the very light to the vigorous intensity domains. LT testing is more submaximal than the 6MWT, and is a valuable tool to estimate the ˙VO2max in older male adults. Implementation of LT testing in physical activity programs might help improving the quality of aerobic exercise training in older men.
Keywords: aerobic threshold; cardiorespiratory exercise testing; endurance assessment; exercise-intensity domains; fixed-percentage approach